The effectiveness of snowball throwing technique in teaching reading comprehension at SMPN 6 tolitoli - khuznainy, khuznainy; Indrawati, Indah; Firmansyah, Moh (Universitas Madako Tolitoli, 2023)
The effectiveness of using the snowball throwing method to teach descriptive texts in order to improve reading comprehension in ninth-grade students at SMPN 6 Tolitoli is discussed in this study. This study focuses on how well children can read descriptive literature. This study aims to determine whether the snowball throwing method in teaching reading comprehension to third-grade children at SMPN 6 Tolitoli is effective. The participants in this study were ninth-grade students at SMPN 6 Tolitoli. This study is an experimental study. This study was conducted in one class. The snowball throwing method was used to teach descriptive texts to the experimental class, and pre- and post-tests with research instruments were used to collect data. The pre- and post-tests were normally distributed and had the same variance based on the findings of the normality test study. The paired sample t-test is another formula used to examine the data. This was done to see if there was a difference in the overall average score of the experimental class. Statistics show that the average pre-test score of the experimental group was 41.45. The average post-test score of the experimental class was 77.35. A significance value (2-tailed) of 0.000 × 0.05 was achieved using paired-sample T. There is a difference between the mean scores of the post-test and pre-test because Ho is rejected and Ha is accepted. In conclusion, the Snowball Throwing technique effectively teaches descriptive texts in reading comprehension to ninth-grade students in the 2023/2024 academic year.